“MELAMPAUI DUNIA LATIN : KEMURIDAN DAN KEWARGAAN DALAM TEOLOGI PUBLIK KEKRISTENAN ASIA” - James Haire (Institut Filsafat dan Teknologi Kreatif Ledalero, 2011)
Abstract: This article looks at the issues of discipleship and citizenship in the context of Asian Christianity in terms of “belonging”. The concept of discipleship refers to the concept of belonging within the church, while the concept of citizenship refers to belonging within the nation-state. Thus the issue of belonging within these two spheres is a sub-set of the questions relating to public theology within Asian Christianity. The first issue considered is the question as to what extent the assumptions of public Christian theology actually are the assumptions of post-Enlightenment western Christian theology alone, and therefore have only very indirect links with Asian Christianity. The second issue is the intercultural nature of Christian theology, and its implications for public theology, including discipleship and citizenship. The third issue is the reality of Asian society and Asian Christian theology, particularly public theology. Where Christianity is a minority (albeit, large minority), what is the contribution of a public Christian theology to the debates of civil society? In this section the author looks at the concrete reality of violence in Asia, and seek to analyse how the dynamics of Pauline theology frequently used in Asia engage with the fact of violence. Finally the article seeks to answer the question as to what we can learn from Asian Christian contexts on the interaction of faith and culture in relation to Christian discipleship and engaged citizenship. Keywords: kekristenan, budaya, teologi publik, gereja, lokal, global, Asia, reformasi.